A non-associated constitutive model based on yld2004-18p yield criterion and its applications on sheet metal forming analysis - Honghao Wang; Changxiang Fan; Akira Yoshimura; Sai Xu; Guangjun Qiu; Xin Liang; Jun Yanagimoto (Scientific Reports)
Abstract For sheet metals, anisotropy is a significant property affecting sheet metal forming processes. The anisotropy of sheet metals is caused by the rolling process, and several anisotropic constitutive models have been proposed under the non-associated flow rule to describe the deformation and stress anisotropies of sheet metals independently. However, most of them are based on yield functions that are only identified by the experimental data of orthogonal axes, or yield functions that are applicable to only the plane stress state. In this study, the yld2004-18p yield function, which can be used to analyze the three-dimensional stress state in multiple axes with high accuracy and acceptable identification cost, is used to develop a non-associated constitutive model and subsequently applied to sheet metal forming analysis. Finite element analysis results of circular cup drawing and hole expansion demonstrate the capability of the yld2004-18p-based non-associated constitutive model in more accurately describing both the deformation and stress anisotropies of sheet metals.